Traditional Games Festival in International Schools as an Effort to Conservation Indonesian Culture - Kurniawan, Wahyu Ragil; Pramono, Harry; Suripto, Agus Widodo; Bestari, Shinta Della (Universitas Negeri Semarang, 2024)
Conservation of Indonesian culture is still a challenge for the nation's future generations. The educational level is a strategic space to realize educational efforts and cultural preservation, one of which is traditional games. Semarang Multinational School, one of the international schools in the city of Semarang, is a location for service with the main problem being the absence of educational activities and introductions to traditional Indonesian games at the school, and a request from the school to collaborate in implementing traditional games programs at the school. The method used includes the stages of Planning, Screening, Implementation, Evaluation and Reporting. Some types of activities carried out are playing with various types of traditional games including; Dakon, Jump Rope, Bedhil Bambu, Egrang Batok, and Egrang Bambu. The service team received a satisfactory response from the school principal, teachers, parents and students who did it themselves. The results of the activity were a satisfied partner response and the signing of a cooperation document between the Faculty of Sports Science, Semarang State University, and Semarang Multinational School as a partner. Suggestions for similar service can of course be applied anywhere according to field needs, taking into account the common goal of preserving Indonesian culture